Drug Supplies Planning in Hospital for Epidemic Attack using SEIR Model. (July 2019) - Syahrir, Irwan; Suparno; Vanany, Iwan
Abstract: Denguehaemorrhagic fever is one of the epidemic diseases that often occurs in Indonesia. The incidence of dengue outbreaks in Indonesia territory shows an increasing trend from year to year. People infected dengue virus, if not treated immediately can cause death and can quickly spread on a wider scale. The hospital as one of the health care facilities must be able to handle patients who are indicated and infected with dengue quickly and precisely. One important resource is the fulfilment of drug supplies for the treatment of DHF patients. Lack of drugs during a dengue epidemic should not occur because it will seriously endanger patient safety. To avoid shortages of drugs, hospital management is required to be able to manage and determine the enough amount of drug supplies in the hospital. This study aims to predict the amount of drug supplies in hospitals during the outbreak of dengue fever. SEIR model is used to predict the number of drug needs that must be provided by the hospital in the event of an dengue fever outbreak.